Efikasi Intervensi Suplementasi Zat Gizi terhadap Pencegahan Stunting pada Anak Usia < 5 tahun - Studi Literatur - Ardianti, Belinda; Sumarmi, Sri (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2023)
Stunting is a chronic nutritional problem in children under five whose nutritional status is measured based on height for age. One of the efforts to prevent stunting is through intervention or nutritional supplementation. In this review, we will discuss some of the efficacy of supplementation interventions in children under 5 years of age as an effort to reduce the incidence of stunting. This literature review was carried out through a search for journals on the PubMed database in the last 10 years (2011-2021) which resulted in 15 journals that fall into the inclusion criteria in this review. The results of the review show that there are 4 nutritional supplementation intervention methods applied to children under 5 years, including zinc supplementation, LNS supplementation (Lipid-Based Nutrient Supplements), MNP supplementation (Micronutrient Powder) and vitamin D supplementation. Zinc and MNP supplementation interventions, the results showed that there was no effect between the intervention group and the control group on the incidence of stunting or linear growth in children. While the LNS supplementation method, the majority of journals show that there is a significant effect on reducing the incidence of stunting in children. This is because LNS is a supplementation product that combines macro and micro nutrients so that the handling of stunting or for prevention is more optimal. This literature study conclude intervention that has high efficacy in reducing the incidence of stunting is LNS supplementation.